2005
DOI: 10.1161/01.str.0000185703.88944.7d
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Paraoxonases as Candidate Genes for Stroke

Abstract: Background and Purpose-The paraoxonases are involved in protecting low-density lipoprotein (LDL) from lipid oxidation. Paraoxonase 1 (PON1) was implicated in susceptibility to coronary artery disease and stroke in previous studies. We evaluated, in a comprehensive way, all 3 paraoxonase genes for association with stroke observed in the Cholesterol and Recurrent Events (CARE) trial. Methods-Over 2500 subjects enrolled in the CARE trial were genotyped for 14 single nucleotide polymorphisms, including 7 newly ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 33 publications
2
25
0
2
Order By: Relevance
“…[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] Liu et al in 2013 conducted and published a systematic review and meta-analysis of 28 selected studies addressing these relationships. 21 They found that the R allele and the RR genotype of PON1 Q192R polymorphism correlated with a higher risk for ischemic stroke in the general population.…”
Section: Pon1 and Ischemic Strokementioning
confidence: 99%
“…[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] Liu et al in 2013 conducted and published a systematic review and meta-analysis of 28 selected studies addressing these relationships. 21 They found that the R allele and the RR genotype of PON1 Q192R polymorphism correlated with a higher risk for ischemic stroke in the general population.…”
Section: Pon1 and Ischemic Strokementioning
confidence: 99%
“…Studies assessing the significance of PON1 polymorphisms as risk factors of stroke in Asian populations have consistently shown that the Q192R [6, 7] and L55M polymorphisms influence the risk of this disease [8]. The R allele of the PON1 gene Q192R polymorphism was also found to be a risk of stroke in Caucasian stroke victims in North [9] and South [10] America. However, 2 studies performed on Caucasians in Europe did not show such a correlation [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…A positive association of Gln192Arg PON1 polymorphism and IS was described in the metaanalyses and in five case-control studies [177,178,184,185,188], but this association was negative in all other reports. Only two studies in Turkish populations obtained evidence for a positive association of Leu55Met PON1 polymorphism and IS [188,193], in contrast to 12 where no evidence for this association was found [28,30,[177][178][179]181,186,187,[190][191][192]194].…”
Section: Paraoxonase(pon)mentioning
confidence: 99%
“…Almost all research groups except one [192] agree that there is no significant association between IS and these polymorphisms [28,30,177,181,187,199] Four polymorphisms in the PON3 gene were examined in two studies on IS patients [181,187]. No evidence for an association was obtained.…”
Section: Paraoxonase(pon)mentioning
confidence: 99%